2021
DOI: 10.3390/nano11092187
|View full text |Cite
|
Sign up to set email alerts
|

On Improving Wear Resistance of Cr-Al-N Coatings Using Dynamic Glancing Angle DC Magnetron Sputtering

Abstract: The development of alternatives for wear protection in surface engineering can be responsible for a significant decrease in energy waste as a large amount of the energy produced in the world is lost due to tribological contact. Dynamic Glancing Angle Deposition has been recently evaluated as a route to produce coatings with improved wear performance. In this technique, the substrate oscillates along with a determined range in front of the sputtering target during the growth of the film. In this study, five osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…All diffracted peaks corresponded to the face centered cubic (fcc) CrN phase. The absence of peaks related to Cr 2 N or AlN phases showed that aluminum occurs as a substitutional element without phase segregation or AlN precipitation [ 17 , 25 , 26 ]. In addition, all the peaks presented a slight shift to the left (i.e., toward smaller 2θ angles).…”
Section: Resultsmentioning
confidence: 99%
“…All diffracted peaks corresponded to the face centered cubic (fcc) CrN phase. The absence of peaks related to Cr 2 N or AlN phases showed that aluminum occurs as a substitutional element without phase segregation or AlN precipitation [ 17 , 25 , 26 ]. In addition, all the peaks presented a slight shift to the left (i.e., toward smaller 2θ angles).…”
Section: Resultsmentioning
confidence: 99%
“…The properties of coatings can be modified by changing HiPIMS process parameters such as bias polarization, working pressure, gas ratio, substrate displacement, and impinging angle of ion bombardment [ 9 , 16 , 17 , 18 , 19 , 20 , 21 ]. The microstructure, mechanical and tribological behavior are strongly related to N 2 /Ar flow ratios during deposition.…”
Section: Introductionmentioning
confidence: 99%
“…This work is based on the influence of nitrogen and yttrium additions on the microstructure, mechanical and tribological properties in the microstructural, mechanical, and tribological analysis of multilayer (Cr, Y)Nx coatings deposited by HiPIMS on AISI 304L stainless-steel substrates, using Dynamic Glancing Angle Deposition (DGLAD); DGLAD is a manufacturing route to develop nanostructured coatings with increased wear resistance and high hardness and toughness values due to systematic nanostructured layer formation [ 9 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%